Better jobs and incomes in Bulgaria - Molnar, Margit (OECD Economics Department Working Papers, 2023)
The shrinking number of workers due to smaller young cohorts entering the labour market and large-scale outward migration are undermining Bulgaria's growth prospects, the sustainability of its social institutions and society more widely. Bulgaria needs to provide more support for families and make staying in the country more attractive by raising productivity, fostering the creation of more good-quality formal jobs and reinforcing the social safety net. Bulgarian women have high activity rates, a high share in management jobs and a low wage gap with men, but all this translates into high opportunity costs for educated women of having children. Policies, including access to affordable quality childcare countrywide, more egalitarian burden sharing with men and greater incentives to get back to work, would help reduce those costs. Women from disadvantaged backgrounds should be offered a career path through upgrading skills and lifelong learning. Inactivity rates among the working age population should be addressed by reforms to the social welfare system that would improve activation and through targeted measures. Vulnerable groups, including ethnic minorities, are disadvantaged in multiple ways and need tailored measures to escape poverty, acquire skills and integrate into the labour market